Electron scattering from atomic gallium - Fursa, Dmitry; Bray, Igor (Institute of Physics Publishing Ltd., 2009)
Recently the non-relativistic convergent close-coupling method has been extended into the relativistic domain [1]. When applied to electron impact collision processes for highly charged hydrogen-like ions, the RCCC method that utilizes relativistic kinematics and the Coulomb interaction in the absence of QED Breit and Mller corrections is suitable for target ions with atomic number Z up to Z 30. For Z larger than 30, such QED corrections become significant and must be included in the calculations. We have modified the RCCC computer code accordingly and report the results for Z = 100 selected excitation cross sections and for U91+ ionization cross sections which were found to be in good agreement with previous calculations of Fontes et al.[2].